Régimes de temporalités et mutation des temps sociaux - Claude Dubar (Temporalités)
This article develops the hypothesis that temporal systems change according to the sphere of social activity being considered (work or private life) and the relationship between time and subjectivity (free time, imposed time...). On the basis of much empirical researches bearing on, among others, the reduction of working time, training and learning periods, the management of urban living..., the author examine the idea that a radical change concerning time in society is under way, as modernity heretofore based on work passes in another phase, as yet cloaked in confusion and uncertainty.